Diagnostic Utility of the Wechsler Adult Intelligence Scale – Fourth Edition (WAIS-IV) Among Elders with Alzheimer’s Dementia - Made Syanesti Adishesa; Magdalena S. Halim (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
The aim of this study was to examine the diagnostic utility of the Indonesian version of Wechsler Adult Intelligence Scale Fourth Edition (WAIS-IV-ID) in classifying between typical aging and Alzheimer’s dementia (AD). We administered the WAIS-IV-ID to 47 AD patients (28 females and 19 males; mean age 68 ± 8 years). Severity of dementia was classified into three categories: mild (20 patients), moderate (13 patients), and severe (14 patients). On the basis of receiver operatic characteristic (ROC) analysis, the areas under the curve (AUCs) of each index are as follows: (a) .83, 95% CI [0.738, 0.895] for Full IQ, (b) .88, 95% CI [0.81, 0.94] for Perceptual Reasoning, (c) .79, 95% CI [0.69, 0.86] for Processing Speed, (d) .78, 95% CI [0.69, 0.86] for Verbal Comprehension, and (e) .71, 95% CI [0.61, 0.8] for Working Memory. These AUC values indicate that the WAIS-IV-ID has moderate accuracy in identifying people with AD. This study also raised awareness for the necessity of a standardized process in translating and using cognitive tests, especially in clinical practices.